Producción y procesamiento del maíz en Colombia (2013)
Corn has become one of the most worldwide consumed grains. It is primarily used for food and feed. Also, in order to replace the use of oil and its derivatives which are non-renewable resources, as raw material in the production of industrial and food starch, in the production of sweeteners, dextrin, oil and other byproducts of fermentation such as ethanol, industrial alcohol, carbon dioxide (CO2), amino acids, antibiotics and plastics. To obtain these products, it is carried out a wet milling process which involves a series of important steps for the production of starch and its derivatives. This review is related to the origin, structure, and processing of corn and some of its applications derivatives.